Mind what teacher says: Teachers' propensity for mental‐state language and children's theory of mind in middle childhood. Issue 2 (25th August 2021) - Lecce, Serena; Ronchi, Luca; Devine, Rory T.
Abstract: This study examined the link between theory of mind (ToM) in middle childhood and teachers' propensity for mental‐state language and self‐reported conversational‐instruction strategies. Multilevel analyses on 430 Italian children (221 girls,   Mage   = 9.34 years,   SD   = .63, Range: 7.95–11.43 years) from 27 primary‐school classrooms and their teachers showed that: (i) there were striking between‐classroom differences in children's ToM; (ii) teachers' propensity for mental‐state language (β = .14) and self‐reported conversational‐instruction strategies (β = .16) were uniquely associated with pupils' ToM even when child‐related (i.e., age, verbal ability, number of siblings and SES) and teacher‐related variables (i.e., ToM, verbal ability and years of experience) were controlled; and (iii) the association between self‐reported conversational‐instruction strategies and ToM was significant in older children and smaller classrooms. These findings extend socio‐cultural accounts of ToM by showing a developmental continuity of environmental effects on children's ToM.